Karakteristik Komposit Bioplastik dalam Variasi Rasio Maizena-Glukomanan dan Jenis Pemlastis - Wisnawa P, I Pt Cahya; Harsojuwono, Bambang Admadi (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2021)
This study aims to determine the effect of variations in the ratio of cornstarch-glucomannan and types of plasticizer on the characteristics of bioplastic composites to produce the best bioplastic composites. This study uses the two factorial randomized block design. The first factor is the variation in the ratio of cornstarch-glucomannan which consists of three levels, namely 5:1 ; 4,5:1,5 ; 4:2. The second factor is the type of plasticizer, namely glycerol, sorbitol, and propylene glycol. Each treatment was devided  into two groups based on the time of making the bioplastic, so that 18 experimental units are obtained. The variables observed were tensile strength, elongation at break, elasticity, swelling, and biodegradation. The  data  obtained  were  analyzed  for  diversity  and  continued  with  a  test  of  Significant  Honest Difference. The results show that the variation of the cornstarch-glucomannan ratio and the type of plasticizer and their interactions had a very significant effect on tensile strength, elongation at break, and elasticity. The variation in the ratio of cornstarch-glucomannan and the type of plasticizer had a very significant effect, but the interaction had a significant effect on swelling. The best bioplastic characteristics are found in the variations of cornstarch-glucomannan (4:2) with the type of glycerol plasticizer with a tensile strength value of 5.685 MPa, elongation at break of 20,110%, elasticity of 26,735 MPa, swelling of 1.149%, duration of degradation is 6 days. Keywords:  bioplastics, cornstarch-glucomannan ratio, glycerol, propylene glycol , sorbitol